Teorie pochodzenia Pulcinelli i jego związki z antykiem - Sterna, Marta (Collectanea Philologica, 2015)
A discussion on the origin of Pulcinella, the most important mask of Neapolitan Theatre, is the subject matter of the following article. At the beginning, I will present the characteristics of this figure including his symbolism. Then, I will discuss possible connections of Pulcinella with some dramatic forms of ancient theatre. At the same time, I will describe a review of study of this figure specifying the most important phases of this research. The conclusion of this article will consist of the summary of the results of carried out analysis.